"Social justice is a dream": Tensions and contradictions in nursing education. Issue 5 (5th June 2019) - Valderama‐Wallace, Claire P.; Apesoa‐Varano, Ester Carolina
Abstract: Objective: The purpose of this study was to explore nurse educators' conceptualizations of social justice in theory courses. The findings contextualize the role of nurse educators in promoting social justice among future health care providers and the relevance of their perspectives on social justice. Design: This descriptive qualitative study was completed utilizing constructivist grounded theory methods. Sample and Measurements: I interviewed 28 nurse educators teaching theory courses in Baccalaureate nursing programs on the West coast of the United States. Initial and focused codes were constructed from interview transcripts to understand and contextualize statements about social justice. Results: Participants' conceptualizations of social justice include equity, equality, self‐awareness, withholding judgment, and taking action. Conclusions: Notable differences emerged along racial lines and, less so, in relation to educational background and nursing specialty. This study highlights areas of concern with respect to how nurse educators enact the claim that social justice is a core professional nursing value. The findings call attention to tensions and contradictions as individuals navigate the landscape of nursing with limited structural and institutional effort.